1 : 3‐Resonance in a Hopf–Hopf bifurcation. Issue 1 (21st October 2015) - Steindl, Alois
Abstract We investigate the bifurcating solutions at a Hopf–Hopf interaction point with an internal 1 : 3 resonance. It turns out, that the transitions from single to mixed modes can be described by Duffing or Mathieu szenarios. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)